PERFORMANCE AND COEFFICIENT OF DIGESTIBILITY FEED OF BALI PIGS OFFERED FERMENTED OF RICE BRAN - I K. H., Valentino; Putri, T. I.; Budaarsa, K. (Jurnal Peternakan Tropika; Vol 5 No 2 (2017), 2017)
This study aims to determine the effect of giving feed containing fermented rice bran on the performance and coefficient of digestibility of feed of the pigs. This research was conducted for 12 weeks at the research farm Faculty of Animal Husbandry Udayana University and Proximate analysis at the Nutrition and Feed Laboratory of Udayana University Faculty of Animal Husbandry. Livestock used is bali pigs females weaning with average weight 17.75 ± 2.08 kg of 16 tails. This research used Randomized Block Design with 4 groups as replication and 4 treatments among others were feed non-rice bran fermentation (RA), feed with rice bran fermentation 15% (RB), feed with rice bran fermentation 22.5% (RC), and feed with rice bran fermentation 30% (RD). The variables observed were feed consumption, weight gain, FCR, dry matter digestibility coefficient, organic matter, crude protein, crude fiber, ether extract, and energy. The results showed that the dry matter digestibility coefficient, organic matter, crude fiber, energy, and FCR were not significantly different (P>0.05) among all treatments, while the feed consumption, body weight gain, crude protein digestibility coefficient and ether extract, show significant higher results (P<0,05) on RC and RD treatment compared with RA and RB. The results of this study can be concluded that the treatment of RC and RD can increase the feed consumption, body weight gain, crude protein digestibility coefficient, and ether extract.  Keywords : bali pigs, rice bran fermentation. coefficient of digestibility feed, performance of pig,